Prevalence of anemia in Somalia: A systematic review and meta-analysis of 3988 participants - Yahye Ahmed Nageye; Abdirasak Sharif Ali Mude; Kizito Eneye Bello (Iraqi Journal of Hematology)
The incidence of anemia in Somalia is of medical concerns, especially among neonates and pregnant women. Despite the available intervention of the government to provide iron-based supplement, the associated morbidity of anemia in Somalia is still of medical relevance. This systematic review and meta-analysis were conducted to provide detailed information on the prevalence of anemia in Somalia. A systematic search for articles describing the prevalence of anemia within Somalia was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-analysis guidelines. A meta-analysis was performed on our eligible studies using the random effect model. Our search returned 13 eligible articles involving 3988 participants within Somalia. There was a relative high prevalence of anemia in Somalia in this study 39.7% (95% CI: 26.3–53.1; I2=99.26%, P≤ 0.001). A higher proportion of these cases was from pregnant women. Cross-sectional study designs had more incidence of anemia 39.8% (95% CI: 29.0–51.7) than retrospective studies 29.2% (95% CI: 17.0–45.3) in this review. There was a variation in the distribution of anemia in relation to the publication years at P< 0.001. Evidence from this study reveals that there is a high prevalence of anemiain Somalia and effort toward strategic treatment should be prioritized.